Risk Management - Sarfraz, Muddassar; Ivascu, Larisa (IntechOpen, 2021)
Risk management is a very important process in the context of global and organizational sustainability. It helps organizations prepare for organizational risks and reduce costs before they occur. Risk management contributes to the achievement of organizational objectives and to the development of organizational benefits and risk opportunities. As such, this book identifies strategic challenges for risk management assessment and practices, examines potential factors that affect business growth, and offers new opportunities for enterprises. It includes fifteen chapters that cover such topics as sustainable management in the construction industry, risk communication in the age of COVID, managing tax risks in mergers and acquisitions, corporate governance, and much more.